Silencing the self across cultures depression and gender in the social world - Jack, Dana Crowley; Ali, Alisha, 1970- (New York ; Oxford : Oxford University Press, 2010)
Offering new perspectives on social and psychological aspects of the complex dynamic of depression, the authors use Silencing the Self theory, which details the negative psychological effects when individuals silence themselves in close relationships and the importance of the social context in precipitating depression.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Depression in women -- Cross-cultural studies